Catheter-Related Bloodstream Infections among patients on maintenance haemodialysis: a cross-sectional study at a tertiary hospital in Ghana - Bismark Opoku-Asare; Vincent Boima; Vincent Jessey Ganu; Elvis Aboagye; Olive Asafu-Adjaye; Anita Ago Asare; Isaac Kyeremateng; Edward Kwakyi; Adwoa Agyei; Eric Sampane-Donkor; Peter Puplampu (BMC Infectious Diseases, 2023)
Abstract Background Catheter-Related Bloodstream Infections (CRBSIs) are notable complications among patients receiving maintenance haemodialysis. However, data on the prevalence of CRBSIs is lacking. This study was conducted to determine the prevalence and factors associated with CRBSIs among patients receiving haemodialysis in the renal unit of the largest tertiary hospital in Ghana. Methods A hospital-based cross-sectional study was conducted on patients receiving maintenance haemodialysis via central venous catheters (CVC) between September 2021 and April 2022. Multivariate analysis using logistic regression was used to determine the risk factors that were predictive of CRBSI. Analysis was performed using SPSS version 23 and a p-value<0.05 was statistically significant. Results The prevalence of CRBSI was 34.2% (52/152). Of these, more than half of them (53.9%(28/52)) had Possible CRBSI while 11.5% (6/52) had Definite CRBSI. Among the positive cultures, 62% (21/34) were from catheter sites whilst the rest were from peripheral blood. Gram-negative cultures made up 53% (18/34) of positive cultures with the rest being Gram positive cultures. Acinetobacter baumannii (33.3% (6/18)) was the commonest organism isolated among Gram-negative cultures whilst Coagulase negative Staphylococci (43.7% (7/16)) was the commonest organism isolated among Gram-positve cultures. Gram-negative bacilli were more predominant in this study making up 52.9% of the total bacteria cultured. Sex, duration of maintenance dialysis, underlying cause of End-stage kidney disease, mean corpuscular haemoglobin (MCH), neutrophil count and lymphocyte count were significantly predictive of CRBSI status (p<0.05). Conclusion There was a high prevalence of CRBSI among patients undergoing haemodialysis. The commonest causative agent was Coagulase negative Staphylococci, however there was a predominance of Gram-negative bacilli as compared to Gram positive cocci. There is a need to set up infection surveillance unit in the renal unit to track CRBSI and put in place measures to reduce these CRBSI.